Zakat Fund Model In Developing Micro, Small And Medium Enterprises (Msmes) In Ponorogo Through Capital, Human Resource And Religiousity As Mediating Variable - Atika R. Masrifah; Furqan hifdzur rahman (Journal of Islamic Economics and Philanthropy, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. MSMEs account for nearly ninety percent of all Indonesian businesses. MSMEs, which account for nearly half of all businesses in Indonesia, have enormous potential to boost the Indonesian economy. However, MSMEs, particularly micro enterprises, face challenges in running their businesses. Capital is an issue that always occurs in MSMEs. Access to capital loans has always been a barrier in the operation of small businesses, particularly Micro Enterprises. To Adress this productive zakat funds are one type of Instrument can assist MSMEs in facing barier acces to fund. This study attempt to examine the effect of productive zakat on developing MSMEs and what factors can affect MSMEs' growth. The quantitative approach is used in this study, and the research method is SEM (Structural Equation Modeling) used as analysis of techniqal. The results of this study indicate that the variables of capital and human resources have a significant and positive effect on the development of MSMEs. while zakat funds have a significant and negative effect on mustahik capital and religiosity. This shows that if the productive zakat increases, mustahik capital and mustahik religiosity will decrease. The suggestion from this research is that monitoring of productive zakat distribution needs to be improved and it is hoped that it will be more selective in giving to mustahik.Keywords: Zakat, MSMEs, SEM